2023
DOI: 10.3389/fpubh.2023.1204064
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of targeted next-generation sequencing for the diagnosis of drug-resistant tuberculosis in low-resource settings: a programmatic model, challenges, and initial outcomes

Abstract: Targeted next-generation sequencing (tNGS) from clinical specimens has the potential to become a comprehensive tool for routine drug-resistance (DR) prediction of Mycobacterium tuberculosis complex strains (MTBC), the causative agent of tuberculosis (TB). However, TB mainly affects low- and middle-income countries, in which the implementation of new technologies have specific needs and challenges. We propose a model for programmatic implementation of tNGS in settings with no or low previous sequencing capacity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Only primary quantitative studies were selected from the search output. The title of the study, year of study, study setting, study design, MDR-TB confirmed number of cases, MDR-TB/HIV co-infection proportion, and the outcome explored were characteristics retrieved from the studies (Table 1 ) [ 9 13 , 14 ▪▪ , 15 21 , 22 ▪▪ , 23 , 24 ▪▪ , 25 29 , 30 ▪ , 31 ▪ , 32 36 , 37 ▪▪ , 38 48 , 49 ▪▪ , 50 ▪ ].…”
Section: Search Methodsmentioning
confidence: 99%
“…Only primary quantitative studies were selected from the search output. The title of the study, year of study, study setting, study design, MDR-TB confirmed number of cases, MDR-TB/HIV co-infection proportion, and the outcome explored were characteristics retrieved from the studies (Table 1 ) [ 9 13 , 14 ▪▪ , 15 21 , 22 ▪▪ , 23 , 24 ▪▪ , 25 29 , 30 ▪ , 31 ▪ , 32 36 , 37 ▪▪ , 38 48 , 49 ▪▪ , 50 ▪ ].…”
Section: Search Methodsmentioning
confidence: 99%
“…The difficulties faced in implementing tNGS are ubiquitous amongst all low- and middle-income countries. A recent strategy that has been successfully implemented in Nigeria utilised a model comprising preparation, implementation, and sustainability phases [ 37, 38 ]. The preparation phase involved site and staff identification, establishing a timeline with achievable goals, with effective co-ordination, communication and contracting.…”
Section: Challenges To the Deployment Of Tngs In South Africamentioning
confidence: 99%
“…The benefits associated with tNGS extend beyond TB diagnostics [ 37, 38 ]. The implementation of NGS and tNGS infrastructure will upskill the molecular workforce of the country.…”
Section: Challenges To the Deployment Of Tngs In South Africamentioning
confidence: 99%
“…The design of primers or probes for enrichment necessitates an in-depth understanding of the genomic characteristics of the organisms under investigation. An inaccurate selection of target regions can result in incomplete or biased results [56,57]. Furthermore, data analysis and interpretation can be complex, especially when dealing with diverse microbial populations.…”
Section: Targeted Sequencingmentioning
confidence: 99%
“…A programmatic model for the implementation of tNGS has been put into action in Namibia, an upper middle-income country located in Southern Africa. Namibia faces a significant burden of tuberculosis (TB) [56]. The overarching goal of integrating tNGS into routine practices in high-TB-incidence countries, such as Namibia, is to enhance the clinical management of TB cases and establish effective surveillance mechanisms for resistance to new treatment regimens.…”
Section: Targeted Sequencingmentioning
confidence: 99%